Building Smart Village Governance Beyond Technology: Evidence From a Participatory Action Research on OpenSID Implementation in Indonesia - Saadah, Mar Atun; Yanti, Ovie; Setiawan, Wahyu Juari; Syeftiani, Try; Permana, Kurnia; Hendriyaldi, Hendriyaldi; Muhammad Haris (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to strengthen village governance capacity through mentoring and assistance in implementing the digital Village Information System (OpenSID) as part of Indonesia’s Smart Village agenda. The program focuses on improving administrative services, data management, and community participation at the village level. Using a Participatory Action Research (PAR) approach, the program was conducted in Jujun Village and involved village officials, community members, local government representatives, and digital platform developers. The intervention consisted of sequential stages, including policy socialization on the role of the Village Information System in smart governance, capacity-building workshops for village officials, hands-on technical assistance in operating OpenSID, and community outreach to promote SID-based public services. Evaluation was conducted two weeks after implementation using qualitative indicators encompassing knowledge, attitudes, skills, partnership dynamics, and follow-up commitment. The findings indicate improvements in digital literacy and operational capacity among village officials, as well as increased community awareness of digital public services. However, the program also revealed limitations in sustaining digital transformation, particularly related to managerial commitment, leadership-driven institutionalization, and resource ownership. Stakeholder participation was evident but often remained normative rather than transformative. Overall, this community service initiative contributes to ongoing discussions on digital governance and rural development by demonstrating that technology adoption alone is insufficient to achieve smart governance outcomes. Instead, sustained impact depends on participatory capacity building and the development of dynamic managerial capabilities that enable villages to institutionalize digital governance practices over time.